Development 68Ga trastuzumab Fab and bioevaluation by PET imaging in HER2/neu expressing breast cancer patients. Issue 4 (7th February 2022) - Rathore, Yogesh; Shukla, Jaya; Laroiya, Ishita; Deep, Amar; Lakhanpal, Tamanna; Kumar, Rajender; Singh, Harmandeep; Bal, Amanjit; Singh, Gurpreet; Gopal Thakur, Krishan; Mittal, B R
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Receptors on breast cancer cells play a crucial role in the management of patients. Trastuzumab is a widely used drug for the treatment of HER2/neu expressing tumors. ImmunoPET with trastuzumab is not feasible due to slow pharmacokinetics. Fragment of antigen-binding (Fab) radiolabeled with positron emitters can be used for immunoPET. Methods: Fab has been generated by papain digestion and conjugated with the bifunctional chelating agent NOTA. The SDS-PAGE and MALDI-TOF were used to see the integrity of Fab and conjugated Fab. In-vitro stability and target specificity for HER2/neu receptors were performed in plasma and receptor binding with bio-layer interferometry (BLI) techniques. Radiolabeling was standardized with 68 GaCl3 and PET imaging was performed in seven patients showing 18 F fluorodeoxyglucose ( 18 F-FDG) uptake and correlated with HER2/neu expression by immunohistochemistry. Results: Fab production was optimized at molar ratio 23:1 of trastuzumab and papain at 37 °C with a constant stirrer at 850 rpm for 22-24 h, at pH 8. Conjugation with NOTA was standardized at molar ratio 1:25 of trastuzumab Fab and NOTA. Molecular mass of trastuzumab Fab-NOTA was found approximately 46.3 kDa ( 1/3 of intact antibody). Trastuzumab Fab-NOTA showed radiolabelling efficiency of 48-70% with incubation time 15 min at 37-40 °C and pH 4.5–5.0. BLI demonstrated the affinity of trastuzumab, trastuzumab Fab and trastuzumab Fab-NOTA towards HER2/neu receptor with KD of <1pM, 0.5nM and 20nM, respectively. All immunohistochemistry proven patients showed uptake in primary breast lesion and lymph nodes. Conclusion: Trastuzumab Fab-NOTA is suitable for radiolabelling with 68 Ga and ImmunoPET imaging of HER2/neu receptor.